2011
DOI: 10.1111/j.1365-2095.2010.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary inclusion of various plant ingredients as an alternative for Sargassum thunbergii on growth and body composition of juvenile sea cucumber Apostichopus japonicus

Abstract: Two feeding experiments were conducted to investigate the effects of dietary inclusion of different plant ingredients on growth and body composition of juvenile sea cucumber. In the first experiment, three replicate groups of the sea cucumber (average weight of 1.5 ± 0.05 g) were fed one of the seven experimental diets containing Sargassum thunbergii (CON), Undaria (UND), Laminaria (LAM), Brassica oleracea L. var. capitata (BRA), fermented soybean (FSB), distillers dried grain (DDG) and rice straw powder (RIC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 20 publications
4
57
2
3
Order By: Relevance
“…DDG has already been tested as a possible alternative protein and/ or energy source associated with aquafeed (Chevanan et al, 2010;Wu et al, 1996), and it is less expensive than traditional ingredients such as soybean meal and wheat flour (Rahman et al, 2013a(Rahman et al, , 2013b. Seo et al (2011) reported that rice-based DDG contains a high protein content and well-balanced amino acid profile, and may be useful for producing low-cost feed for juvenile olive flounder (Rahman et al, 2013a) and sea cucumber (Choi et al, 2013). Therefore, the objective of the this study was to investigate the effects of dietary DDG as an alternative feed ingredient (compared to traditional soybean meal and wheat flour) on the growth and body composition of juvenile abalone.…”
Section: Experimental Animal and Feeding Experimentsmentioning
confidence: 99%
“…DDG has already been tested as a possible alternative protein and/ or energy source associated with aquafeed (Chevanan et al, 2010;Wu et al, 1996), and it is less expensive than traditional ingredients such as soybean meal and wheat flour (Rahman et al, 2013a(Rahman et al, , 2013b. Seo et al (2011) reported that rice-based DDG contains a high protein content and well-balanced amino acid profile, and may be useful for producing low-cost feed for juvenile olive flounder (Rahman et al, 2013a) and sea cucumber (Choi et al, 2013). Therefore, the objective of the this study was to investigate the effects of dietary DDG as an alternative feed ingredient (compared to traditional soybean meal and wheat flour) on the growth and body composition of juvenile abalone.…”
Section: Experimental Animal and Feeding Experimentsmentioning
confidence: 99%
“…Hal ini menunjukkan bahwa teripang pasir mempunyai keterbatasan untuk mencerna rumput laut. Nilai kecernaan pakan ini hampir sama dengan yang dilaporkan Seo et al (2011) yaitu berkisar 41%-50% untuk bahan kering dan 65%-76% untuk kecernaan protein pakan (tujuh jenis pakan) yang menggunakan tepung Sargassum thunbergii sebanyak 20%-40%, tepung kedelai dan dikombinasikan dengan tepung rumput Undaria pinnatifida atau Laminaria japonica untuk teripang A. japonicus.…”
Section: Kontrol Controlunclassified
“…Shi et al (2013) juga menggunakan alga coklat Sargassum thunbergii sebagai pakan pada budidaya teripang Apostichopus japonicus (Selenka) di Cina, karena alga ini mempunyai kandungan protein yang cukup untuk kebutuhan protein teripang, yaitu 7,8%-11% dan kaya akan asam amino. Beberapa jenis rumput laut lainnya yang juga digunakan pada pemeliharaan teripang Apostichopus japonicus (Selenka) adalah Undaria pinnatifida (Seo et al, 2011), Gracilaria lemaneiformis (Gao et al, 2011), dan Ulva lactuca (Xia et al, 2012a). Bahkan Xia et al (2012b) melaporkan pakan yang mengandung 50% Laminaria japonica dari total alga dalam pakan sangat cocok untuk budidaya teripang Apostichopus japonicus.…”
Section: Kontrol Controlunclassified
See 1 more Smart Citation
“…However, limited information is available on the effect of dietary DDG from rice as an alternative ingredient for juvenile abalone, H. discus hannai. Our previous studies suggested that DDG from rice could improve the growth performance of sea cucumber (Seo et al, 2011;Choi et al, 2013).…”
Section: Experimental Animal and Feeding Experimentsmentioning
confidence: 99%